The Role of Green Roofs and Living Walls as WSUD Approaches in a Dry Climate - Simon, Beecham; Mostafa, Razzaghmanesh; Rosmina, Bustami; James, Ward (Elsevier, 2019)
The addition of green infrastructure, including green roofs and living walls, into buildings is part of a new approach to urban design aimed at resolving current problems associated with built environments. Green roofs and living walls are becoming an important component of water sensitive urban design systems, and their use around the world has increased in recent years. Green roofs can cover the impermeable roof areas that densely populate our urban areas, and through doing so, can provide many environmental, economic, and social benefits. In addition to roofs, there are a number of bare walls that have the potential to be transformed into vegetated, living walls. Living walls can potentially improve air quality, reduce pollution levels, reduce temperatures inside and outside of buildings, reduce building energy usage, and improve human health. Despite such benefits, both green roofs and living walls are relatively new technologies, and there are several research gaps and practical barriers to overcome before these systems can be applied more widely. Furthermore, specific design criteria need to be developed for a range of climatic conditions to develop resilient green infrastructure. Consequently, several field experiments comprising both intensive and extensive green roof test beds, as well as living walls, have been recently established. In these recent research studies, stormwater quality and quantity, hydrological behavior, plant performance, and thermal benefit have been investigated. The findings of these studies can be used to identify the key elements of resilient green roof and living wall systems.